Multiscale coupling coordination analysis and spatial heterogeneity between blue-green space landscape stability and environmental pressures in Nanchang, Jiangxi Province, China - Duan, Mingming; Luo, Dan (Frontiers in Earth Science, 2025)
Understanding the interaction between blue-green space stability (BGSS) and environmental pressures (EPs) is critical for urban ecological resilience. This study developed blue-green space stability index (BGSSI) and environmental pressure indexes (EPIs) to explore their coupling coordination and spatial heterogeneity across four spatial scales (1 km, 5 km, 10 km grids, and administrative districts) in Nanchang City, China. We integrated local bivariate Moran’s I, spatial regression, and a Coupling Coordination Degree Model (CCDM) to evaluate their spatial relationships. Results show that: 1) The distribution of EPIs and BGSSI exhibits spatial heterogeneity, with high pressure and low stability in the central part of the city, while in contrast, mountainous and forest areas in the suburbs had low pressure and high stability. 2) The spatial clustering results of EPIs and BGSSI indicated that the blue space represents low-low clusters as ecologically sensitive areas, the middle of the city represented high-low clusters as ecologically dangerous areas, and the green space represented low-high clusters as important ecological protection areas. The spatial regression indicated that EPIs were negatively correlated with BGSSI, and spatial autocorrelation and spatial spillover effects were observed between them, economic and population pressures have lower coefficients than other factors. 3) EPIs and BGSSI exhibited three stages and nine types of coordinated coupling relationships. As the grid expands, the proportion of Running-in stage (RS) increases, while the proportion of Coordination stage (CS) decreases. Our multiscale analysis reveals the bidirectional, scale-sensitive nature of EPs–BGSS interactions and provides a methodological framework to guide differentiated ecological planning and spatial governance.